Pengaruh Financial Attitude dan Lifestyle Terhadap Personal Financial Management (Studi pada Kalangan Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Pendidikan Indonesia) - Wulandari, Suci; Purnamasari, Imas; Sulastri, Sulastri (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This study aims to analyze the influence of financial attitude and lifestyle on personal financial management among undergraduate students of the Faculty of Economics and Business, State University in Bandung City. The research method used in this study is a descriptive method and a verification method with the unit of analysis being undergraduate students of the Faculty of Economics and Business, State University in Bandung City with a population of 11,704 students and a sample of 352 respondents using purposive sampling with software IBM SPSS AMOS version 22 for Windows. The data was processed using the Structural Equation Modeling (SEM) method. The results of the study indicate that financial attitude and lifestyle have a significant and positive effect on personal financial management both partially and simultaneously, this is indicated by the magnitude of the critical ratio which is greater than the minimum value. The implications of the study indicate that the better the financial attitude and the more positive the lifestyle of the undergraduate students, the better the ability in personal financial management among undergraduate students of the Faculty of Economics and Business, State University in Bandung City. In addition, the results of this study can also be a basis for educational institutions and the financial industry to develop educational programs and services that support strengthening financial attitudes and a wiser lifestyle. By understanding these dynamics, undergraduate students at the Faculty of Economics and Business, State University in Bandung City can develop appropriate strategies in managing their personal finances.